A study of production and consumption of certain foodstuffs in South Africa during the period 1929-49, in relation to the increase in population and national income - Baker, G C (Rhodes University, Faculty of Commerce, Department of Economics, 1936)
From Introduction: South Africa has experienced an almost revolutionary change in her food position in the last 10 years, what was previously a "farm problem" of assisting the primary producer has now become a "food problem" and this is a study of the development of those factors leading up to such a change. It is an empirical study attempting to measure the production and consumption of certain selected foodstuffs and to compare them with changes observed in the population and the National Income.
Keywords: Food consumption -- South Africa; Food supply -- South Africa